Response characteristics of vegetation and soil environment to permafrost degradation in the upstream regions of the Shule River Basin - Shengyun Chen; Wenjie Liu; Xiang Qin; Yushuo Liu; Tongzuo Zhang; Kelong Chen; Fengzu Hu; Jiawen Ren; Dahe Qin (Environmental Research Letters, 2012)
Permafrost degradation exhibits striking and profound influences on the alpine ecosystem, and response characteristics of vegetation and soil environment to such degradation inevitably differ during the entire degraded periods. However, up to now, the related research is lacking in the Qinghai–Tibetan Plateau (QTP). For this reason, twenty ecological plots in the different types of permafrost zones were selected in the upstream regions of the Shule River Basin on the northeastern margin of the QTP. Vegetation characteristics (species diversity, community coverage and biomass etc) and topsoil environment (temperature (ST), water content (SW), mechanical composition (SMC), culturable microorganism (SCM), organic carbon (SOC) and total nitrogen (TN) contents and so on), as well as active layer thickness (ALT) were investigated in late July 2009 and 2010. A spatial–temporal shifts method (the spatial pattern that is represented by different types of permafrost shifting to the temporal series that stands for different stages of permafrost degradation) has been used to discuss response characteristics of vegetation and topsoil environment throughout the entire permafrost degradation. The results showed that (1) ST of 0–40 cm depth and ALT gradually increased from highly stable and stable permafrost (H-SP) to unstable permafrost (UP). SW increased initially and then decreased, and SOC content and the quantities of SCM at a depth of 0–20 cm first decreased and then increased, whereas TN content and SMC showed obscure trends throughout the stages of permafrost degradation with a stability decline from H-SP to extremely unstable permafrost (EUP); (2) further, species diversity, community coverage and biomass first increased and then decreased in the stages from H-SP to EUP; (3) in the alpine meadow ecosystem, SOC and TN contents increased initially and then decreased, soil sandy fractions gradually increased with stages of permafrost degradation from substable (SSP) to transitional (TP), and to UP. Meanwhile, SOC/TN storages increased in the former stage, while they decreased in the latter stage. This study indicated that the response characteristics of vegetation and soil environment varied throughout the entire permafrost degradation, and SW was the dominant ecological factor that limited vegetation distribution and growth. Therefore, SSP and TP phases could provide a favourable environment for plant growth, mainly contributing to high SW.